Global Financial Stability and the Lessons of History: A Review of Carmen M. Reinhart and Kenneth S. Rogoff's This Time Is Different: Eight Centuries of Financial Folly - Taylor, Alan M (Journal of Economic Literature, 2012)
In Reinhart and Rogoff's economic history This Time is Different, the authors provide a panoramic view of crises from the Middle Ages to the modern era. Published just as the current global financial storm arrived, the book quickly showed how history could provide not just useful perspective but also, as we can now see, very prescient guidance in the aftermath. In the longer run, the book serves to inspire ongoing work in long-run macro-financial history. (JEL F30, G01, G20, N20)